Rancang Bangun Sistem Penyusunan Jadwal Pelajaran Menggunakan Algoritma Genetika Berbasis Web (study Kasus MI Mahalul Ulum) - Rudianto, Agus; Muhandhis, Isnaini (Journal of System Engineering and Technological Innovation, 2022)
Scheduling subjects is the most important administrative activity carried out at the beginning of the semester in the academic year, making the schedule of subjects is not very easy many aspects that affect and have to be calculated, this can be an obstacle for the schedule maker and causes the making of the schedule to be a rather long process because a conflicting teacher. To overcome this problem, a web-based scheduling system was built using the algorithm method, with the limits determined, this algorithm is expected to be able to solve this problem well without any teacher schedule constraints that clash with other schedules. By collecting data through observation and interviews with the principal, then the data obtained by using the genetic algorithm approach to the formulation of the algorithm can also produce a pretty good schedule and can divide the teaching hours of certification teachers and ordinary teachers as well. Approach with Genetic Algorithm in solving the problem of scheduling subjects can be successfully applied with a good combination. The Scheduling System can divide JTM well so that the teaching hours supported by certification teachers have exceeded more than 24 JTM in one week.